GROWTH RETARDATION OF CHICK EMBRYO EXPOSED TO A LOW DOSE OF ELECTROMAGNETIC WAVES - Siddiqi, Najam; C, Muthusami John; Norrish, Mark; Heming, Thomas (Journal of Ayub Medical College Abbottabad, 2016)
Background: The objectives of this study were to explore the effects of low dose of the non-ionizing (REW) emitted by a mobile phone on the development of chick embryo. Methods: one hundred and twenty chick fertilized eggs were equally divided into a control and an exposed group. Sixty fertilized eggs were placed in an egg incubator with a mobile phone (SAR US: 1.10W/kg (head) 0.47 W/kg body) in silent mode having vibration disable mode. Mobile was called for a total of 20 minutes in 24 hours. Twenty embryos each were sacrificed at day 5, 10 and 15, mortality, wet body weight, head to rump length, eye diameter and morphological changes were noted. The control group, 60 eggs were incubated in the same conditions, having removed the phone. Results: No mortality was noted. The experimental group exposed to REW showed subcutaneous haemorrhagic areas and significant growth retardation at day 10 as evidence by smaller eye diameter, wet weight and CR length than the control group. There were no significant growth differences at either day 5 or at day 15. Conclusion: Electromagnetic waves emitted from mobile phones even though for a very short duration of 20 minutes per day have affected the growth of the chick embryo at day 10 of incubation, Hence exposure of these waves are not 100% safe. Keywords: electromagnetic waves, chick embryo, mobile phone, egg incubator, growth retardation